Anonymous trust management scheme of VANET based on attribute signature - Min XIAO; Faying MAO; Yonghong HUANG; Yunfei CAO (网络与信息安全学报)
Trust management mechanisms can solve the authenticity assessment problem of messages and establish trust between communication entities in the VANET.However, current trust management schemes lack an effective privacy protection mechanism, leading to privacy concerns for vehicles when binding their identity with their trust level.Based on the anonymity of attribute-based signature, an anonymous trust management scheme was proposed for VANET.The trust level of the vehicle was maintained by the trusted authority.The trust level of vehicles and the current time were taken as the attribute identity set of the vehicle, so as to realize the binding of the anonymous vehicle identity with its trust level, which could provide the privacy protection of vehicles.In addition, the timely update of attribute signature private key could resist false reputation attack and the trust level of the vehicle could be verified anonymously while the attribute signature was verified.Furthermore, the pseudonym was used to hide the real identity of the vehicle, enabling only the trusted authority could parse the real identity of vehicles from the pseudonym to update their trust level, and providing legal and secure tracking of the malicious vehicle identity vehicle.Under the general group model, the attribute-based signature scheme is proven to satisfy the security of unforgerability.The security analysis further shows that the scheme protects the identity and location privacy of vehicles, enables only the trusted authority to legally track malicious vehicles, resists false reputation attacks, ensures communication integrity, and resists replay attacks.Performance analysis confirms that the proposed scheme has better computation and communication efficiency than existing schemes.